2006
DOI: 10.1111/j.1365-2265.2006.02639.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with somatostatin analogues on QT interval duration in acromegalic patients

Abstract: Acromegalic patients frequently display an abnormally prolonged QT interval, a known risk factor for potentially fatal arrhythmias. Treatment of these patients with SSA is able to improve and even normalize this alteration, probably contributing to the beneficial effects of these drugs on cardiac rhythm in this endocrine disorder. The inclusion of octreotide in the list of drugs that may increase QTc should be reconsidered as regards its indication in acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 24 publications
(54 reference statements)
5
51
2
2
Order By: Relevance
“…In literature, the number of studies showing lengthened QT intervals in patients with acromegaly is uncommon. [16][17][18][19] As consistent with previous ones, it was demostrated in our study that baseline QT max, QT dispersion, QTc max and QTc dispersion were longer, compared to controls. Lengthening of QT intervals in patients with acromegaly can be explained by the direct effects of GH and IGF-1 on myocardium or left ventricular hypertrophy due to DM, HT and similar disorders.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In literature, the number of studies showing lengthened QT intervals in patients with acromegaly is uncommon. [16][17][18][19] As consistent with previous ones, it was demostrated in our study that baseline QT max, QT dispersion, QTc max and QTc dispersion were longer, compared to controls. Lengthening of QT intervals in patients with acromegaly can be explained by the direct effects of GH and IGF-1 on myocardium or left ventricular hypertrophy due to DM, HT and similar disorders.…”
Section: Discussionsupporting
confidence: 91%
“…20 Fatti et al also detected no correlation between GH and IGF-1 levels, and pre-and post-treatment QTc intervals. 17 As consistent with Fatti et al, Unubol et al observed no correlation between GH and IGF-1, and QTc dispersion. 18 In our study, a correlation was detected only between GH and post-treatment QTc dispersion.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Electrocardiographic QT complex (QTc) interval (which is significantly longer in patients with active acromegaly and can contribute to fatal arrhythmias) was significantly shortened and normalized after 3-63 months octreotide LAR or lanreotide SR treatment, along with reduction of heart rate. Six patients with acromegaly had pathologically prolonged QTc which normalized after treatment (Fatti et al, 2006).…”
Section: Symptom Controlmentioning
confidence: 99%
“…Fatti et al [Fatti et al 2006] detected abnormally long QTc interval before treatment in one-quarter of 30 acromegalic patients in a retrospective study.…”
Section: Short-term Variability Of Qt Interval In Patients With Acrommentioning
confidence: 99%